A carbohydrate-grafted nanovesicle with activatable optical and acoustic contrasts for dual modality high performance tumor imaging1. Issue 3 (16th March 2015) - Wu, Xuanjun; Lin, Bijuan; Yu, Mingzhu; Yang, Liu; Han, Jiahuai; Han, Shoufa
<x xml:space="preserve">Abstract</x> High-performance illumination of subcutaneous tumor and liver tumor foci was achieved with sialic acid-targeted acid-responsive nanovesicles which become fluorescent and photoacoustic upon internalization into tumor lysosomes.